2012
DOI: 10.3126/saarctb.v9i1.6958
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of the NTP to DOTS recommended defaulters tracing mechanism in Khyber Pakhtunkhwa, Pakistan

Abstract: Introduction: Tuberculosis is still a major public health problem worldwide. Pakistan is one of the few countries with extremely high tuberculosis (TB) incidence and ranks sixth among the 22 high TB burden countries. World Health Organization (WHO) and International Union Against Tuberculosis and Lung Diseases (IUATLD) advocate the use of DOTS strategy to control tuberculosis. The study aimed to determine the adherence of DOTS facilitators and treatment supporters to the defaulter tracing mechanisms in Khyber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…2 Similarly, a study done in Sri Lanka showed that old age population were more prone to relapse, defaulter and treatment failure. 3 More than two-thirds (82%) of respondents were male which is consistent with study done in Pakistan by Afridi et al 4 This might be due to the reason that women had less access to diagnostic facilities than men. As well, males traveled more in areas of studies conducted.…”
Section: Resultssupporting
confidence: 85%
“…2 Similarly, a study done in Sri Lanka showed that old age population were more prone to relapse, defaulter and treatment failure. 3 More than two-thirds (82%) of respondents were male which is consistent with study done in Pakistan by Afridi et al 4 This might be due to the reason that women had less access to diagnostic facilities than men. As well, males traveled more in areas of studies conducted.…”
Section: Resultssupporting
confidence: 85%